Challenges University Students face in eLearning as a result of the covid19 pandemic - Mmbwanga, Florence; Simiyu, Evelyn Etakwa; Maroko, Geoffrey (Machakos University Press, 2021)
The emergence of Covid-19 pandemic in early 2020 has had adverse effects all over the world, not just health wise, but in agriculture, transport and even education. The partial and total lockdown in many counties across the world has brought many economies to near stagnation. In Kenya, like in many countries the world over, all learning institutions were shut down as a precautionary measure to curb the spread of covid19. eLearning was introduced in most universities to sustain the education sector and ensure that learners go on with their studies in a safe environment. The aim of the current research was to investigate the challenges university students face in eLearning as a result of the covid19 pandemic with a focus of highlighting the hindrances towards adoption of the same within the universities. The study used a qualitative research design. Purposive sampling was used to get students involved in eLearning in five universities across the country. The data collected was analyzed using thematic and narrative analyses. Applied research was carried out during this study so as to highlight the challenges university students face in eLearning around the world and recommend the best practices for adoption of the same in learning institutions.
Keywords: Covid-19; Pandemic; E-Learning; Challenges